2013
DOI: 10.1186/1750-1172-8-51
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis type VI phenotypes-genotypes and antibody response to galsulfase

Abstract: BackgroundMucopolysaccharidosis type VI (Maroteaux-Lamy syndrome; MPS VI) is an autosomal recessive lysosomal storage disorder in which deficiency of N-acetylgalactosamine 4-sulfatase (arylsulfatase B; ARSB) leads to the storage of glycosaminoglycans (GAGs) in connective tissue. The genotype-phenotype correlation has been addressed in several publications but the picture is not complete. Since 2007, enzyme-replacement therapy (ERT) has been available for patients with MPS VI in the Netherlands. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 27 publications
1
45
0
2
Order By: Relevance
“…In our study, both twins showed negative results, despite higher levels of total antibodies in Twin 1, probably associated with the increased basal levels of the endogenous enzyme. In other lysosomal diseases, the antibody levels in the blood can affect the efficacy of the ERT by inhibiting the uptake of the enzyme by the target tissues (Brands et al 2013). Our results show no galsulfase antibodies in MPS VI patients, so the marked signs and symptoms might be only associated with the rapid, progressive form of the disease.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our study, both twins showed negative results, despite higher levels of total antibodies in Twin 1, probably associated with the increased basal levels of the endogenous enzyme. In other lysosomal diseases, the antibody levels in the blood can affect the efficacy of the ERT by inhibiting the uptake of the enzyme by the target tissues (Brands et al 2013). Our results show no galsulfase antibodies in MPS VI patients, so the marked signs and symptoms might be only associated with the rapid, progressive form of the disease.…”
Section: Discussionmentioning
confidence: 57%
“…In particular, the left ventricular hypertrophy and functional abnormalities of the mitral and aortic valves are progressive in individuals who are not treated (Braunlin et al 2013). These abnormalities are stabilized by galsulfase treatment (Brands et al 2013;Giugliani et al 2014). We found mild mitral insufficiency in both twins, although mitral valve regurgitation is described in most MPS VI pediatric reports (Azevedo et al 2004;Scarpa et al 2009;Fesslova et al 2009;Lael et al 2010).…”
Section: Discussionmentioning
confidence: 65%
“…Among these, Emre and colleagues characterized biochemically and genetically a group of MPS patients including three MPS VI cases . Recently, Brands described four MPS VI patients of Turkish ethnogeographic origin (Brands et al 2013). Hence this is the first study reporting the molecular characterization of the ARSB mutations in a quite large group of Maroteaux-Lamy cases from Turkey.…”
Section: Discussionmentioning
confidence: 84%
“…Through the in vitro expression of the mutated protein they evidenced a slightly reduced amount of the 66 kDa ARSB precursor, while they did not detect the 46 kDa mature form of the enzyme (Brands et al 2013).…”
Section: Genotype-phenotype Correlationmentioning
confidence: 96%
See 1 more Smart Citation